2022
DOI: 10.2166/wh.2022.302
|View full text |Cite
|
Sign up to set email alerts
|

Determination of salt concentration in water using decision trees and electromagnetic waves

Abstract: Salt water adversely affects human health and plant growth. In parallel with the increasing interest in non-contact determination of salt concentration in water, a novel approach is proposed in this study. In the proposed approach, S parameter measurements, which show the scattering properties of electromagnetic waves, are used. First, the relationship between salt concentration in water and permittivity values, a distinguishing feature for liquids, is shown. Then, based on the derived correlations from a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This observed decline in model performance after conducting 10-fold cross-validation is consistent with the findings of a separate study that investigated the prediction of salt concentration in water samples. The study identified a decision forest algorithm as the most effective classifier in that context [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…This observed decline in model performance after conducting 10-fold cross-validation is consistent with the findings of a separate study that investigated the prediction of salt concentration in water samples. The study identified a decision forest algorithm as the most effective classifier in that context [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here the author's state that the averaged BOD and COD are related and can lead to a far more precise and effective study. The authors [16] describe an optimized random forest method for the categorization of arsenic (As) levels in groundwater samples taken from the Indo-Gangetic area. The gradient boost approach is recommended by the authors of [17] for BOD prediction.…”
Section: Introductionmentioning
confidence: 99%
“…This provides the possibility of generating and transferring energy between biological molecules and this realizes the phenomenon of life and causes the occurrence of biological anomalies of water in living organisms (features of electrical conductivity, freezing, etc.). However, the mechanisms for realizing this important role of water as an integral component of the magnetoelectrochemical basis of the phenomenon of life at the molecular level in living biological systems have long remained undiscovered and are still being studied [3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%